Évaluation des politiques environnementales accompagnant les projets autoroutiers : cas de l’a75 et via egnatia - Lamara Hadjou (VertigO)
The projects of building new highways are often accompanied by environmental measures to preserve the areas impacted. These traditional measures are a regulatory obligation under the responsibility of concessionary companies, in the case of conceded highways, and the state if they are not under concessions. In recent years a new highway policy has been developed in France, passing from the stage of catching up to one of planning. Rural and fragile areas isolated from the major transport networks, because of their lack of profitability, now benefit from road projects with a view to planning. The nature of the territories crossed, often mountainous and sensitive areas with unique landscapes, led the actors to think about a new support policy, taking into account both the areas directly crossed and those beyond the highway. In this paper, we try to discuss these developments with emphasis on innovations and the role of the local milieu. The latter has often been omitted, even though its mobilization is essential in the implementation of environmental policies. We take the case of the highway A75 in France and the Via Egnatia in Greece to establish a European comparison.